ROLE OF C- PEPTIDE IN IDENTIFICATION OF PATIENTS SUSPECTED OF HAVING LATENT AUTOIMMUNE DIABETES IN ADULTS (LADA) IN NORTH INDIAN TYPE 2 DIABETES MELLITUS POPULATION. - SHAKTI AGGARWAL,; ATUL GOEL,; ANJU JAIN, (International Journal of Pharma and Bio Sciences, 2010)
Aims: The objective of this study was to utilize C - peptide levels to identify the patients suspected of having latent autoimmune diabetes in adults from clinically diagnosed type 2 diabetics. Methods:100 type 2 DM patients and 100 healthy controls were selected. All patients were assessed for fasting Cpeptide and insulin levels. Patients having C-peptide level<0.7 ng/ml were classified as suspected LADA subgroup. All patients were followed up six months later for fasting C- peptide and insulin levels along with insulin resistance. Results: 34% of the patients in the study group were classified as suspected LADA group while the rest of the patients in the study group (n = 66) were named as classic type 2 DM. There was a significant difference in the levels of C – peptide and insulin as well as insulin resistance between the suspected LADA group and classic type 2 DM patients, which was maintained on, follow up. Conclusions: C-peptide can be used as an important screening tool for autoimmunity.